Redistributing income through hierarchy - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2021)
Although the determinants of income are complex, the results are surprisingly uniform. To a first approximation, top incomes follow a power-law distribution, and the redistribution of income corresponds to a change in the power-law exponent. Given the messiness of the struggle for resources, why is the outcome so simple? This paper explores the idea that the (re)distribution of top incomes is uniform because it is shaped by a ubiquitous feature of social life, namely hierarchy. Using a model first developed by Herbert Simon and Harold Lydall, I show that hierarchy can explain the power-law distribution of top incomes, including how income gets redistributed as the rich get richer.
Keywords: E13; C01; O47; 330; corporation; despotism; government; hierarchy; income; distribution; inequality; power